1998
DOI: 10.1063/1.475360
|View full text |Cite
|
Sign up to set email alerts
|

The dipole bound-to-covalent anion transformation in uracil

Abstract: Articles you may be interested inOxygen cluster anions revisited: Solvent-mediated dissociation of the core O4 − anion Zwitterion formation in hydrated amino acid, dipole bound anions: How many water molecules are required?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
252
3
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(276 citation statements)
references
References 21 publications
20
252
3
1
Order By: Relevance
“…And furthermore, the solvation of the uracil anionic state by one water molecule provides an extra stabilization of this state by ca. 0.4 eV [58,59]. Thus, the solvation of U − by the amino acid would have to provide an extra stabilization of 1.3 eV to be consistent with the maxima of the PES peaks at 1.8 eV, which is again improbable.…”
Section: Bfpt In Binary Complexes Of Nucleobases With Proton Donorsmentioning
confidence: 92%
See 1 more Smart Citation
“…And furthermore, the solvation of the uracil anionic state by one water molecule provides an extra stabilization of this state by ca. 0.4 eV [58,59]. Thus, the solvation of U − by the amino acid would have to provide an extra stabilization of 1.3 eV to be consistent with the maxima of the PES peaks at 1.8 eV, which is again improbable.…”
Section: Bfpt In Binary Complexes Of Nucleobases With Proton Donorsmentioning
confidence: 92%
“…On the other hand, it is well known that the valence anions of nucleobases, unstable in the gas phase [33], become adiabatically stable due to even marginal solvation. For instance, employing photoelectron spectroscopy (PES) Bowen et al [34] demonstrated that isolated uracil forms a stable dipole bound anion (DB). When it interacts with the argon atom both DB and valence anions are registered, and for uracil complex with single water molecule only the valence anion signal appears in the PES spectrum.…”
Section: Dna Damage Induced By Low Energy Electronsmentioning
confidence: 99%
“…There exist two types of radical-anion states of nucleobases: ͑i͒ dipole-bound anions where the excess electron is located far outside the molecule and ͑ii͒ valence ͑co-valently bound͒ anionic state the electron is delocalized over the molecule. The existence of dipole-bound anions was first predicted theoretically by Adamowicz and co-workers 14,15 and subsequently detected in the gas-phase experiments by Desfrançois et al 16 and Hendricks et al 17,18 In the gas phase, the nucleobase anions may be described as electron-dipolebound states. [19][20][21] However, it has been shown that hydrogen bonds between an anion and its surroundings stabilize the valence-bound state.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior evidently indicates that the anion state of band I is a e s À state, since dipole-bound anions usually exhibit a relatively flat trend in electron binding energy with increase in the cluster size and can survive only at low values of n. Besides, the VDEs of band I (0.5-1.1 eV for n ¼ 10-100) are higher than those of dipole-bound anions, which are typically much lower than 0.2 eV. 78,108,109 Consistently, the formation of e s À was experimentally confirmed in liquid CH 3 CN. 104,105 Recent theoretical study of excess electron attachment to CH 3 CN clusters by Takayanagi 114 also supports our assignment.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Another remarkable feature is the large difference in electron binding energy between bands I and II. The coexistence of two different anionic isomers has been reported for several cluster anions, such as (uracil) À Xe, 108 (pyridine) 4 À , 78,79 and (HF) 3 À , 109 in which the differences between VDEs of the isomers have been reported to be %0.2 eV. For the (CH 3 CN) n À clusters, however, the differences between VDEs of bands I and II (%1.8 eV at n ¼ 11-100) are much larger than in these species.…”
Section: Research Backgroundmentioning
confidence: 99%